Autocuidado y riesgos ergonómicos en los trabajadores de la Florícola Rosa de Saron - Cayambe - Cabascango Calapaqui, Nataly Lizbeth (2025)
Self-care and ergonomic risks in workers represent a significant challenge for occupational health and labor productivity worldwide. Workers are exposed to forced body postures, repetitive movements and excessive loads, which produce musculoskeletal disorders that negatively impact wellbeing and performance. This research was focused on analyzing the level of knowledge of self-care and ergonomic risks among the Rosa de Saron flower workers, using a quantitative methodology with an inductive-deductive approach, historic-logic, analytic-synthetic, and systemic. The main instrument used was the survey applied to the workers, and its diagnosis allowed to identify the relevance of the problem. Results demonstrated that 62% of the people surveyed did not attend to medical controls, reflecting a deficiency in preventive health and access to medical services. In addition, 82% did not perform warming routines which increase the risk of muscle injuries, similarly, 66% are not aware of the adequate use of self-protection equipment, 38% reported suffering from discomfort and pains caused by inadequate body postures and physical efforts, finally 81% claimed to suffer from neck pain, back pain and shoulder pain, all of which cause musculoskeletal problems. These results highlight the need to apply educational and preventive intervention. This study also elaborated an educational guide that includes self-care, ergonomic risks and active pauses to lessen risks, prevent injuries and promote labor well-being, contributing to a better and sustainable quality of life among the workers previously mentioned.